2021
DOI: 10.30897/ijegeo.836780
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Aircraft Emissions During Landing and Take-Off (LTO) Cycles at Batumi International Airport, Georgia

Abstract: In this paper, aircraft emissions (nitrogen oxides, carbon monoxide, and hydrocarbons) were estimated during landing and take-off (LTO) cycles for the year 2018 at Batumi International Airport in Georgia. The calculation model is based on flight data recorded by TAV Airports Holding Corporations in Georgia, including type and number of aircraft, engine type, number of passengers, and emission factors from the International Civil Aviation Organization Engine Exhaust Emission Databank were used for estimating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
2
11
0
2
Order By: Relevance
“…Hem eski tip uçaklar olması hem de Dünya sivil havacılık sektöründe en çok kullanılan dar gövde uçaklar olması sebebiyle bu oran yüksektir. Tokuşlu (2021), Batum havaalanında uçakların LTO döngüsünde CO miktarını hesaplamış ve aşağıdaki sonuca ulaşmıştır. AirFrance (2011)'a göre modern uçaklar hem doğayı kirletmemesi hem de performans açısından daha verimlidir.…”
Section: E)unclassified
See 1 more Smart Citation
“…Hem eski tip uçaklar olması hem de Dünya sivil havacılık sektöründe en çok kullanılan dar gövde uçaklar olması sebebiyle bu oran yüksektir. Tokuşlu (2021), Batum havaalanında uçakların LTO döngüsünde CO miktarını hesaplamış ve aşağıdaki sonuca ulaşmıştır. AirFrance (2011)'a göre modern uçaklar hem doğayı kirletmemesi hem de performans açısından daha verimlidir.…”
Section: E)unclassified
“…Sonuçlar, kurumsal sosyal sorumlulukların sosyal veya ekonomik boyutlarından ziyade çevresel konulara daha güçlü bir şekilde odaklanıldığını göstermektedir. Tokuşlu (2021), çalışmasında Gürcistan'daki Batum Uluslararası Havalimanı'nda 2018 yılı için iniş ve kalkış döngüleri sırasında uçak emisyonlarını (azot oksitler, karbon monoksit ve hidrokarbonlar) tahmin etmiştir. Hesaplama modeli, Gürcistan'daki TAV Havalimanları Holding Şirketleri tarafından kaydedilen uçak tipi ve sayısı, motor tipi, yolcu sayısı ve Uluslararası Sivil Havacılık Örgütü Motor Egzoz Emisyonu Veri Bankası'ndaki emisyon faktörleri dahil olmak üzere uçuş verilerine dayanmaktadır.…”
Section: Literatürunclassified
“…The International Civil Aviation Organization (ICAO) predicts that emissions that arise from flying will increase by an average of three times until 2050 (ICAO, 2019). The aviation sector accounts for approximately 3.5% of global carbon dioxide (CO2) emissions (Cohen and Kantenbacher, 2020;Tokuşlu, 2021;Ibrahım and Arouna, 2022;Eskenazi et al, 2022). However, the share of aviation in global CO2 emissions is expected to rise to between 15% and 40% by 2050 since the sector has an average annual growth rate of 5% and faces no constraints on emissions released (Baumeister and Onkila, 2017;Ülker et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is globally observed that there is an increasing deviation in targeted carbon emission reduction levels (50% in 2025 and 80% reduction in 2050 compared to 1990) in line with the Paris Agreement, where the limiting global warming to 1.5-2°C was aimed (Green Construction Board (GCB), 2015). On the road map published by the GCB, it was stated that the reduction of GHG emissions in 2009 was 17% compared to 1990, while it was only 11% in 2012 (GCB, 2015;Tokuşlu, 2021). In addition to its economic share, the construction industry has a significant impact on total GHG emissions with energy consumption and use of resources from the supply chain.…”
Section: Introductionmentioning
confidence: 99%